ASSOCIATION BETWEEN OBESITY AND SERUM URIC ACID LEVELS AMONG COMMUNITY RESIDENTS IN THE CATCHMENT AREA OF THE KOTA TIMUR COMMUNITY HEALTH CENTER, GORONTALO CITY - Aprianingsih R. Djana; Diah Astini Paramita; Rini Daud Supu (Jurnal Ilmiah dr. Aloei Saboe, 2025)
Obesity is a major public health problem associated with metabolic disorders, including hyperuricemia. Excess adiposity may increase serum uric acid levels through insulin resistance and impaired renal urate excretion. However, evidence from Indonesian primary healthcare settings remains limited. This study aimed to determine the association between obesity and serum uric acid levels among community residents in the catchment area of the Kota Timur Community Health Center, Gorontalo City. A quantitative analytical observational study with a cross-sectional design was conducted among 15 obese respondents selected using purposive sampling. Body Mass Index (BMI) was calculated from anthropometric measurements, while serum uric acid levels were measured using capillary blood samples with a Family Dr. Uric Acid Meter. Data were analyzed descriptively, and the association between BMI and serum uric acid levels was examined using the Spearman rank correlation test. Most respondents were female (53.3%) and aged 40–45 years (33.3%). Abnormal serum uric acid levels were found in 53.3% of respondents. The Spearman rank correlation test showed no significant association between obesity and serum uric acid levels (p = 0.592). Obesity, as measured by BMI, was not significantly associated with serum uric acid levels among obese community residents. Further studies with larger sample sizes and additional metabolic and lifestyle variables are needed to clarify this relationship.